Emotional perception of COVID-19 in Mexico: Comparative study between phase 1, phase 2 and the media - Lugo-González, Isaias Vicente (2021)
Background: Since the first COVID-19 cases in Mexico there have been a variety of emotional responses which have in common fear and stress. The emotional impact of COVID-19 is builded in some way because the information flooding parallel to the pandemic phases, the transition between them and illness perception. The aim of the present work was to compare the perception of COVID-19 between phase 1 and 2 of the pandemic and between the information media used to inform themselves in the Mexican population. Methods: Considering a chain sampling, a comparative study was carried out in which an evaluation battery was disseminated through email and social networks, which was answered by 1560 participants. Results: The concern about the consequences of COVID-19 and its emotional impact increased when going from phase 1 to phase 2 of the pandemic. In addition, it was identified that the emotional impact was greater in those who reported through Facebook® and television. Conclusions: The pandemic will have a progressive emotional impact as its phases progress and the importance of informing oneself in adequate means to prevent emotional consequences.